A novel FADS2 isoform identified in human milk fat globule suppresses FADS2 mediated Δ6-desaturation of omega-3 fatty acids. (November 2018) - Kothapalli, Kumar S.D.; Park, Hui Gyu; Guo, Xiaoxian; Sun, Xuepeng; Zou, James; Hyon, Stephanie S.; Qin, Xia; Lawrence, Peter; Ran-Ressler, Rinat R.; Zhang, Ji Yao; Gu, Zhenglong; Brenna, J. Thomas
Highlights: We show expression of 15, 605 transcripts in human milk fat globule (MFG) from a single donor. A novel FADS2 alternative transcript (FADS2AT2) was discovered in MFG. FADS2AT2 is non-catalytic but inhibited FADS2 Δ6-desaturation of omega-3 but not omega-6 PUFA. FADS2AT2 is the first human molecular species that inhibits biosynthesis of one PUFA family but not the other. Abstract: Introduction: The only known non-pharmacological means to alter long chain polyunsaturated fatty acid (LCPUFA) abundance in mammalian tissue is by altering substrate fatty acid ratios. Alternative mRNA splicing is increasingly recognized as a modulator of protein structure and function. Here we report identification of a novel alternative transcript (AT) of fatty acid desaturase 2 (FADS2) that inhibits production of omega-3 but not omega-6 LCPUFA, discovered during study of ATs in human milk fat globules (MFG). Methods: Human breastmilk collected from a single donor was used to isolate MFG. An mRNA-sequencing library was constructed from the total RNA isolated from the MFG. The constructed library was sequenced using an Illumina HiSeq instrument operating in high output mode. Expression levels of evolutionary conserved FADSAT were measured using cDNA from MFG by semi-quantitative RT-PCR assay. Results: RNA sequencing revealed >15, 000 transcripts, including moderate expression of the FADS2 classical transcript (CS). A novel FADS2 alternative transcript ( FADS2AT2 ) with 386 amino acids was discovered. When FADS2AT2 was transiently transfected into MCF7 cells stably expressing FADS2, delta-6 desaturation (D6D) of alpha-linolenic acid 18:3n−3 → 18:4n−3 was suppressed as were downstream products 20:4n−3 and 20:5n−3. In contrast, no significant effect on D6D of linoleic acid 18:2n−6 → 18:3n−6 or downstream products was observed. FADS2, FADS2AT1 and 5 out of 8 known FADS3AT were expressed in MFG. FADS1, FADS3AT3, and FADS3AT5 are undetectable. Conclusion: The novel, noncatalytic FADS2AT2 regulates FADS2CS-mediated Δ6-desaturation of omega-3 but not omega-6 PUFA biosynthesis. This spliced isoform mediated interaction is the first molecular mechanism by which desaturation of one PUFA family but not the other is modulated.